Integrasi Literasi Keuangan dan Kesadaran Lingkungan dalam Pengelolaan UMKM Tajur Halang, Bogor - Subekti, Rini; Praningtyas, Elisabeth Ria Viana; Suryantari, Yulita; Anggya Agustina, Putu Ayu (Universitas Terbuka, 2025)
Home-based food businesses are one form of Micro, Small, and Medium Enterprises (MSMEs) that play a strategic role in supporting family economic resilience. However, in practice, this type of business actor often faces challenges in financial management, especially related to calculating the cost of production (HPP), recording transactions, and selecting packaging that is not only visually attractive but also supports the principles of environmental sustainability. This Community Service (PKM) activity was carried out with the aim of increasing the entrepreneurial literacy of residents, especially in terms of business management and the use of environmentally friendly packaging. The methods used include field observation, interactive counseling, group discussions, and evaluations based on participant feedback. The results of the activity program show that most business actors have not implemented financial records and do not have a distinctive brand identity or product packaging. After the counseling, there was an increase in understanding regarding the importance of separating business and household resources, recording business costs in a structured manner, and using packaging that supports the zero waste movement. This activity program makes a positive contribution to building awareness of more economically and ecologically responsible entrepreneurs among home-based food MSME actors.